ROBO1 is required for postnatal growth and survival - Nicole Aurora Kirk; Ye Eun Hwang; Seul Gi Lee; Juyeon Kang; Kate-Lin Ly; Yong Yu Gan; Sangmyung Rhee; Kee-Beom Kim; Kwon-Sik Park (Genes & Genomics, 2026)
Roundabout guidance receptor 1 (ROBO1) is critical for various processes essential to mammalian development. However, its role in postnatal development and growth remains poorly understood, primarily due to perinatal lethality in knockout models. Robo1 knockout mice on a mixed B6/129S genetic background survive into adulthood and exhibit previously unreported abnormalities across multiple organs. These mice display stunted growth and organ-specific defects, including enlarged lung alveoli, premature hair graying, and diminished subcutaneous fat. Notably, these mice have a reduced lifespan. At 23 days of age, corresponding to the beginning of early puberty in mice, Robo1 knockout mice show significantly reduced plasma levels of growth hormone (GH) and insulin-like growth factor 1 (IGF-1), paralleling decreased expression in the pituitary gland and liver, respectively, compared to wild-type littermates. These findings suggest that ROBO1 contributes to the postnatal development and functional maintenance of multiple organs, with associated modulation of the GH/IGF-1 axis, potentially influencing survival. Further studies with larger cohorts are warranted to elucidate the broader implications of ROBO1 deficiency, particularly in relation to human developmental disorders such as growth hormone deficiencies.